Halal Tourism and the Islamic Socio-Cultural Responsibilities of Domestic Tourists in Indonesia - Azhar Alam; Eka Lutfia Khoirun Nisa; Marissa Grace Haque; Abdelsalam Adam Hamid (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
This study aims to identify and analyze the impact of implementing halal principles and Islamic morality on perceptions of socio-cultural responsibility in halal tourism destinations. The research employs a qualitative descriptive method with a phenomenological approach, incorporating surveys and in-depth interviews with Muslim tourists. The findings reveal that halal principles—such as the provision of halal-certified food, adequate prayer facilities, and environments free from prohibited activities—significantly enhance socio-cultural responsibility. Furthermore, Islamic morality, which emphasizes modesty, honesty, justice, and social care, promotes positive interactions and respect among visitors. This research underscores the importance of integrating Islamic values into tourism management to cultivate socially and culturally responsible destinations. Contributing to the literature on halal tourism and socio-cultural responsibility, the study offers practical insights for destination managers seeking to improve service quality and develop effective marketing strategies. Recommendations include enhancing halal facilities, promoting local economic empowerment, and educating tourists about Islamic values to boost satisfaction and loyalty among Muslim travelers.